Agriculture on the road to industrialization: Conclusion - Mellor, John W. (International Food Policy Research Institute, 1995)
How agriculture grows, the pace at which it grows, and the impact it has on growth of the nonagricultural sector, on poverty and urbanization, and on the quality of the physical environment are highly complex issues. As the preceding chapters demonstrate, many factors influence the pattern of growth in any given country: its physical conditions, public policy, institutions, and, above all, its economic and cultural history. Although it is therefore difficult to draw simple generalizations from the eight case studies in this volume, they illustrate a myriad of interesting relationships that have profound implications for the contribution that agriculture could make to development and that give powerful hints as to how the process might proceed in other contexts.